An extraordinary find? Boa Vista 5, a new early modern ship discovered in Lisbon waterfront (Portugal) - Mendes da Silva, Inês; Nunes, Tiago; Bettencourt, José; Ponce, Mónica; Carvalho, Patricia; Silva, Tiago; Lopes, Gonçalo (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
Discovered in August 2020 and excavated until February 2021, Boa Vista 5 is the best-preserved ship ever found in the riverside area of Lisbon. The wreck was discovered in the limits of an anchorage used since Roman times, abandoned on the beach in the intertidal area sometime in the last quarter of the 17th century. The presence of coconuts suggests an operation area on the Atlantic, probably on the Brazilian routes, a rare example of a merchant ship of this period. In this paper we present the excavation and a first analysis of the ship construction features.